Gambaran Energy Expenditure Berdasarkan Aplikasi Google Fit pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung Angkatan 2022 - Muhammad Jordan; Fajar Awalia Yulianto; Widhy Yudistira Nalapraya (Bandung Conference Series: Medical Science, 2023)
Abstract. Energy expenditure is the process of energy production from the burning of energy substrates (carbohydrates, fats and proteins), consumption of oxygen and production of carbon dioxide. Factors that affect energy expenditure are body weight, height, body composition, age, gender, physical activity, and other factors such as hormones and genetics. The level of physical activity in medical students is low so that the energy expenditure is also low. This energy expenditure is said to be low compared to the Mifflin-St Jeor energy expenditure recommendation formula. This research is a descriptive study with a survey method to see an overview of energy expenditure based on the Google Fit application. The subjects in this study were students of the Faculty of Medicine at the Islamic University of Bandung year 2022 with a total of 39 respondents. The results of this study indicate that the average energy expenditure is 1,301.04 calories/day. The results of this study indicate that the average energy expenditure of students at the Faculty of Medicine, Bandung Islamic University class of 2022 is still below the value of the recommended Miffline-St Jeor formula. Abstrak. Pengeluaran energi adalah proses produksi energi dari pembakaran substrat energi (karbohidrat, lemak, dan protein), konsumsi oksigen, dan produksi karbon dioksida. Faktor yang mempengaruhi pengeluaran energi adalah berat badan, tinggi badan, komposisi tubuh, usia, jenis kelamin, aktivitas fisik, dan faktor lainnya seperti hormonal dan genetik. Tingkat aktivitas fisik pada mahasiswa kedokteran termasuk rendah sehingga pengeluaran energi juga rendah. Pengeluaran energi ini dikatakan rendah dibandingkan dengan rumus rekomendasi pengeluaran energi Mifflin-St Jeor. Penelitian ini merupakan penelitian deskriptif dengan metode survey untuk melihat gambaran pengeluaran energi berdasarkan aplikasi Google Fit. Subjek dalam penelitian ini adalah mahasiswa Fakultas Kedokteran Universitas Islam Bandung angkatan 2022 dengan jumlah 39 responden. Hasil penelitian ini menunjukkan bahwa rata-rata pengeluaran energi mahasiswa Fakultas Kedokteran Universitas Islam Bandung angkatan 2022 masih di bawah nilai rumus rekomendasi pengeluaran energi Mifflin-St Jeor.